Akuntansi Pendapatan berbasis Nilai Kearifan Lokal â€œMopoâ€™o Tanggalo Duheloâ€ - Thalib, Mohamad Anwar (Shafin: Sharia Finance and Accounting Journal, 2024)
This study aims to reveal the values of local wisdom behind the practice of income accounting. The paradigm used in this research is Islam. Ethnomethodology is chosen as the research approach. There are five stages of data analysis; charity, knowledge, faith, revealed information, and courtesy, The results of the study show that currently the daily income of the coachmen is less than in previous years. This is because currently there are many types of transportation that can be chosen by the community. Meanwhile, the coachmen could earn a lot of income when they sell horses. The income earned by the bendi charioteers is based on the value of patience. This value is reflected in the decision of the charioteers to stay in this profession even though their daily income is less than in previous years. This value is created on the basis of the belief that patience is needed in obtaining sustenance from God. In the culture of the Gorontalo people, parents (the elders) often give advice about the importance of patience in living life's problems through the expression (lumadu) mopo'odateo duhelo which means full of patience